2016
DOI: 10.1007/s00330-015-4183-4
|View full text |Cite
|
Sign up to set email alerts
|

Head CT: Image quality improvement of posterior fossa and radiation dose reduction with ASiR - comparative studies of CT head examinations

Abstract: ObjectivesTo evaluate head CT protocol developed to improve visibility of the brainstem and cerebellum, lower bone-related artefacts in the posterior fossa and maintain patient radioprotection.MethodsA paired comparison of head CT performed without Adaptive Statistical Iterative Reconstruction (ASiR) and a clinically indicated follow-up with 40 % ASiR was acquired in one group of 55 patients. Patients were scanned in the axial mode with different scanner settings for the brain and the posterior fossa. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…However, its use in the posterior fossa for clinical-decision making has not been as widely accepted. This is mostly due to physiological factors, such as the beam hardening artefact created by bony interference of the cranial vault, and technical factors such as limited zaxis coverage and high variability between automated perfusion software and CT vendor software (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…However, its use in the posterior fossa for clinical-decision making has not been as widely accepted. This is mostly due to physiological factors, such as the beam hardening artefact created by bony interference of the cranial vault, and technical factors such as limited zaxis coverage and high variability between automated perfusion software and CT vendor software (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Based on data provided by the United Nations Scientific Committee on Effects of Atomic Radiation (UNSCEAR), it is estimated that nearly half a million patients benefit from CT examinations everyday [21]. This widespread CT utilization raised the potential radiation risks particularly in children, such as cancer risk, over-exposures, or unjustified use of imaging [7,[22][23][24][25][26][27][28][29][30][31]. This issue directed recent CT researches and innovations to radiation dose reduction methods with preservation of resulting image quality [5,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many studies have shown that IR algorithms have the potential to reduce the radiation dose of cranial CT scans by 20-45% [1,9,29]. Similarly, in a study using 40% ASIR algorithm for head CT, the total DLP was decreased by 19% with better image quality [28]. Another study scanned pediatric phantoms using 40% ASIR-V with 10% reduction of mA in head CT examination protocol and declared nearly 30% reduction of CTDI vol [6].…”
Section: Qualitative Image Assessmentmentioning
confidence: 93%
“…CT scanning of the abdomen in patients is often complicated with artifacts and it relatively increases noise due to the abdomen being a thick and complex organ. One disadvantage of CT Abdomen is that the resulting image has a high noise level (Guzinski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%